Nanomechanics and Histopathology as Diagnostic Tools to Characterize Freshly Removed Human Brain Tumors - Cieśluk M (Dove Medical Press, 2020)
Mateusz Cieśluk,1 Katarzyna Pogoda,2 Piotr Deptuła,1 Paulina Werel,3 Alina Kułakowska,3 Jan Kochanowicz,3 Zenon Mariak,4 Tomasz Łysoń,4 Joanna Reszeć,5 Robert Bucki1 1Department of Medical Microbiology and Nanobiomedical Engineering, Medical University of Bialystok, Bialystok PL-15222, Poland; 2Institute of Nuclear Physics, Polish Academy of Sciences, Krakow PL-31342, Poland; 3Department of Neurology, Medical University of Bialystok, Bialystok PL-15276, Poland; 4Department of Neurosurgery, Medical University of Bialystok, Bialystok PL-15276, Poland; 5Department of Pathology, Medical University of Bialystok, Bialystok PL-15269, PolandCorrespondence: Robert BuckiDepartment of Medical Microbiology and Nanobiomedical Engineering, Medical University of Bialystok, Mickiewicza 2C, Bialystok 15-222, PolandTel +48 85 784 5483Email buckirobert@gmail.comBackground: The tissue-mechanics environment plays a crucial role in human brain physiological development and the pathogenesis of different diseases, especially cancer. Assessment of alterations in brain mechanical  properties during cancer progression might provide important information about possible tissue abnormalities with clinical relevance.Methods: With atomic force microscopy (AFM), the stiffness of freshly removed human brain tumor tissue was determined on various regions of the sample and compared to the stiffness of healthy human brain tissue that was removed during neurosurgery to gain access to tumor mass. An advantage of indentation measurement using AFM is the small volume of tissue required and high resolution at the single-cell level.Results: Our results showed great heterogeneity of stiffness within metastatic cancer or primary high-grade gliomas compared to healthy tissue. That effect was not clearly visible in lower-grade tumors like meningioma.Conclusion: Collected data indicate that AFM might serve as a diagnostic tool in the assessment of human brain tissue stiffness in the process of recognizing tumors.Keywords: AFM, brain tumors, human tissue rheology, mechanomarkers, glioblastoma